Multi-Objective Optimization of Gas Fractionation Unit Operation. (March 2015) - Hou, Ligang; Su, Chengli; Li, Ping; Cao, Jiangtao
Gas fractionation unit is one of the main processes in refinery industries and consumes a significant portion of energy. Optimal operation of gas fractionation unit could reduce energy consumption and therefore minimize the production cost. This paper reports a real application of multi-objective optimization in a gas fractionation unit, in which energy consumption is minimized and product yield is maximized. The optimization algorithm is based on the non-dominate sorting genetic algorithm and the sequential unconstrained minimization technique. The optimization results show that the yield of product is increased and the energy consumption is reduced in the gas fractionation unit.